Global stability of a multistrain SIS model with superinfection - Attila Dénes; Yoshiaki Muroya; Gergely Röst (Mathematical Biosciences and Engineering)
In this paper, we study the global stability of a multistrain SIS model with superinfection. We present an iterative procedure to calculate a sequence of reproduction numbers, and we prove that it completely determines the global dynamics of the system. We show that for any number of strains with different infectivities, the stable coexistence of any subset of the strains is possible, and we completely characterize all scenarios. As an example, we apply our method to a three-strain model.